The barking ghost - Stine, R. L. (New York : Scholastic, 1995)
When the Holmeses move into a new house deep in the woods, scary things begin to happen.
"An Apple paperback."
RL 4.
8-12.
390
Accelerated Reader AR
Keywords: Horror tales; Ghosts -- Fiction; Dogs -- Fiction; Horror stories